2002
DOI: 10.1038/modpathol.3880542
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of DNA Nonhomologous End-Joining Proteins Ku70 and Ku80 in Melanoma Progression

Abstract: Ku70 and Ku80 heterodimers function as regulatory subunits of the DNA-dependent protein kinase and play a very important role in the repairing of DNA double-strand breaks. Although Ku70 is proposed as a candidate for a tumor suppressor gene, not many data are available on Ku70 and Ku80 expression in human tumors. The main aim of this study was to investigate the expression of Ku70 and Ku80 in the ultravioletinduced lesions-nevus cell nevi, lentigos maligna, and malignant melanomas. Nineteen nevus cell nevi, 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Conversely, it has been suggested that deficient expression or lack of Ku70/Ku80 may result in genomic instability leading to tumourogenesis [41]. Earlier phases of melanoma progression are associated with loss of expression of Ku70/Ku80, and the binding activity of Ku70/Ku80 was reported to be strongly reduced at the advanced tumour stage in breast and bladder tumours [42,43]. There are limited investigations focused on DNA repair proteins in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it has been suggested that deficient expression or lack of Ku70/Ku80 may result in genomic instability leading to tumourogenesis [41]. Earlier phases of melanoma progression are associated with loss of expression of Ku70/Ku80, and the binding activity of Ku70/Ku80 was reported to be strongly reduced at the advanced tumour stage in breast and bladder tumours [42,43]. There are limited investigations focused on DNA repair proteins in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, metastasis is a complex process characterized by subclonal evolution (Fidler, 2002). Indeed, recent studies in a clinical setting have shown that functional dysregulation of Ku70 and Ku80 seems to be of greater biological importance than the loss of expression in metastatic tumor spread (Korabiowska et al, 2002). The mechanism of this dysregulation is not known but might be due to a defect in heterodimerization of Ku proteins which has been shown to have physiological importance for efficient nuclear translocation of each Ku.…”
Section: Characterization and Hypothetical Roles Of The Megs In Melanmentioning
confidence: 98%
“…Mutation carriers have a statistically increased risk of several other cancers [i.e., pancreatic and cervical cancers with BRCA1 (13) and prostate, pancreas, stomach, melanoma, lung, and bladder cancers with BRCA2 (14)]. Decreased protein expression of XRCC5 is also reported for melanoma, cervical, and colon cancers (15). Frequent LOH at the BRCA1, BRCA2, and XRCC5 has been observed in several sporadic cancers other than breast and ovary (i.e., tumors of the colon, pancreas, soft tissue, and lung; refs.…”
mentioning
confidence: 99%